Metacognition in Psychology. Issue 4 (December 2019) - Norman, Elisabeth; Pfuhl, Gerit; Sæle, Rannveig Grøm; Svartdal, Frode; Låg, Torstein; Dahl, Tove Irene
How has the concept of metacognition been used within basic and applied psychological research? We begin our answer by presenting a broad definition of metacognition, a historical overview of its development and its presence in research databases. To assess which function and facets are most frequently addressed within each of the sub-disciplines, we present results from separate literature searches. We then review how metacognition has been defined and empirically explored within selected sub-disciplines in terms of typical research questions, conceptual definitions, how the concept has been measured, and examples of interesting findings and implications. We identify similarities, inconsistencies, and disagreements across fields and point out areas for future research. Our overall conclusion is that it is useful to consider metacognition as a broad umbrella concept across different domains and across basic and applied research. Nonetheless, we recommend that researchers be more specific and explicit about their approach and assumptions whenever using metacognition in their research.